2019
DOI: 10.1177/0269215519837585
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and selection for rehabilitation following acute stroke: a prospective cohort study in Queensland, Australia

Abstract: Assessment and selection for rehabilitation following acute stroke: a prospective cohort study in Queensland, Australia. Objective To describe current practice and investigate factors associated with selection for rehabilitation following acute stroke. Design Prospective observational cohort study. Setting Seven public hospitals in Queensland, Australia. Subjects Consecutive patients surviving acute stroke. Measures Rehabilitation selection processes: assessment for rehabilitation needs, referral for rehabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
1
16
2
Order By: Relevance
“…According to guidelines from around the world, it is recommended that all patients receive early assessment and begin rehabilitation in the stroke unit. This is because early and coordinated rehabilitation is one of the main factors contributing to the positive effects of stroke units 23 . Therefore, patients hospitalized in the stroke unit are more likely to receive rehabilitation assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to guidelines from around the world, it is recommended that all patients receive early assessment and begin rehabilitation in the stroke unit. This is because early and coordinated rehabilitation is one of the main factors contributing to the positive effects of stroke units 23 . Therefore, patients hospitalized in the stroke unit are more likely to receive rehabilitation assessments.…”
Section: Discussionmentioning
confidence: 99%
“…In both Australia and Norway, the median hospital length of stay for acute stroke in recent years has been ve days. The rehabilitation of acute inpatient cases is usually carried out in separate wards or in hospitals that provide care through inpatient rehabilitation facilities, and decisions regarding rehabilitation need to be made early 23,28 . Moreover, recent research has shown that approximately 50% of surviving SAH patients have different levels of injuryrelated neurological impairment and persistent physical, social, emotional, and cognitive di culties that prevent return to independent life and work 5,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Further details of recruitment and data collection for the acute hospital stay, including site characteristics, have previously been published. 16 Demographic and clinical data including premorbid conditions and stroke-related information were extracted from the medical records by trained project officers. Participants were tracked through all rehabilitation episodes provided up to six months after stroke.…”
Section: Methodsmentioning
confidence: 99%
“…25 Although not specifically explored in this project, such a screening process may also minimise variations in access to rehabilitation services which currently rely on ad hoc referral processes. [26][27][28][29] In the group of patients identified by screening alone (ie, those not referred via traditional methods), 24.1% were deemed ready by a rehabilitation physician for transfer to a subacute inpatient rehabilitation facility on the same day or within 1 day of screening. This finding is consistent with New et al, 7 who found that 62.7% of the patients referred and assessed by a rehabilitation consult service was deemed to be ready for transfer to inpatient rehabilitation on the same day of assessment.…”
Section: Lessons and Limitationsmentioning
confidence: 99%